Environmental stressors in health and disease - Fuchs, Jürgen, 1957 June 28-; Packer, Lester (M. Dekker, 2001)
This volume illustrates the impact of environmental oxidants on the tissues of the eyes, lungs and skin, as well as on the immune system. It highlights illnesses, injuries and pathologies induced by pro-oxidant environmental xenobiotics such as inflammation, immune response and carcinogenesis.
Keywords: Stress (Physiology); Active oxygen -- Pathophysiology.; elektronické knihy; electronic books